Lack of didactic materials, an issue when teaching foreign languages at Madre Laura's high school (2022)
The purpose of this research is to analyse the lack of didactic materials as an issue when teaching foreign languages at Madre Laura's High School. The methodology implemented is action research, qualitative and ethnographic through the use of didactic teaching in order to understand and/or explain the behaviour, motivations and reactions of the target population study. For this, different types of data collection were used, such as a survey and a focus group. All results were tabulated separately, however, they were analysed quantitatively by using inferential statistics. As a result, most participants showed improvement during the English learning process therefore, meaningful changes in their English class performance were obtained